Functional and radiological outcomes after bridging therapy versus direct thrombectomy in stroke patients with unknown onset: Bridging therapy versus direct thrombectomy in unknown onset stroke patients with 10‐point ASPECTS. (11th October 2020) - Cappellari, M.; Saia, V.; Pracucci, G.; Sallustio, F.; Gandini, R.; Nappini, S.; Nencini, P.; Vallone, S.; Zini, A.; Bigliardi, G.; Granata, F.; Grillo, F.; et al.
Abstract : Background and purpose: The aim was to assess functional and radiological outcomes after bridging therapy (intravenous thrombolysis plus mechanical thrombectomy) versus direct mechanical thrombectomy (MT) in unknown onset stroke patients. Methods: A cohort study was conducted on prospectively collected data from unknown onset stroke patients who received endovascular procedures at ≤6 h from symptom recognition or awakening time. Results: Of the 349 patients with a 10‐point Alberta Stroke Program Early Computed Tomography Score (ASPECTS), 248 received bridging and 101 received direct MT. Of the 134 patients with 6–9‐point ASPECTS, 123 received bridging and 111 received direct MT. Each patient treated with bridging was propensity score matched with a patient treated with direct MT for age, sex, study period, pre‐stroke disability, stroke severity, type of stroke onset, symptom recognition to groin time (or awakening to groin time), ASPECTS and procedure time. In the two matched groups with 10‐point ASPECTS ( n  = 73 vs. n  = 73), bridging was associated with higher rates of excellent outcome (46.6% vs. 28.8%; odds ratio 2.302, 95% confidence interval 1.010–5.244) and successful recanalization (83.6% vs. 63%; odds ratio 3.028, 95% confidence interval 1.369–6.693) compared with direct MT; no significant association was found between bridging and direct MT with regard to rate of symptomatic intracerebral hemorrhage (0% vs. 1.4%). In the two matched groups with 6–9‐point ASPECTS ( n  = 45 vs. n  = 45), no significant associations were found between bridging and direct MT with regard to rates of excellent functional outcome (44.4% vs. 31.1%), successful recanalization (73.3% vs. 76.5%) and symptomatic intracerebral hemorrhage (0% vs. 0%). Conclusions: Bridging at ≤ 6 h of symptom recognition or awakening time was associated with better functional and radiological outcomes in unknown onset stroke patients with 10‐point ASPECTS. Abstract : In the group of patients with 10‐point ASPECTS, bridging therapy was associated with higher rates of excellent outcome and scucessful recanalization compared with direct MT; no siginificant association were found between bridging and direct MT as regards rate of sICH. In the group of patients with 6‐9‐Point ASPECTS, no siginificant associations were found between bridging and direct MT as regards rates of excellent functional outcome, successful recanalization, and sICH.